Hargomulyo Citizens 'Obstacles in Choosing a Leader - Ardi Ashadi; Widodo Widodo (Almana : Jurnal Manajemen dan Bisnis, 2021)
Citizen Hargomulyo has determined a leader which can be expected to protect its people is more when commutation moment hence people surely hope the leader which will be better in holding governance wheel. At this opportunity is writer starts from a survey later; then communicates with the society either through direct and also through passing media social later; then does conduct this research with the descriptive method qualitative. Hence at this opportunity is a writer will pare and explain what citizen resistance in choosing a leader. Candidate resistance is: Less be recognized although often have socialization to 5%. Socialization less 7%, A lot of promise 13%. Experience in society 4%. Less go into society 9%. Successful Team does not solicit 10%. graceless Successful Team 9%. in government 7%. Education 4% campaign Negative 17% and kinds of resistance in the content of according to elector experience 6%.